L’effet Matthieu Mathilda en sciences - Rossiter, Margaret W. (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2003)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; cours; discipline; discours dominant; europe; patriarcat; premier cycle; pédagogie; périodes historiques; régions géographiques; science; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

Les familles homosexuelles aux États-Unis : dissolution d'un mouvement social ou redéfinition de sa portée politique? - Marche, Guillaume (Revue française d'études américaines, 2003)
Families are a challenge to the lesbian and gay movement in the United States, since homosexuality is largely construed as antithetical to "the family". By creating a wide variety of alternative families gays and lesbians however articulate an identity claim which may not be framed exclusively either in terms of assimilationism, or of differentialism. For this reason these alternative families present American society with a transformative potential which is in a position to exert its influence beyond the bounds of the gay and lesbian community. Far from being a hindrance in terms of efficiency, the very fact that these families constitute a private locus of gay and lesbian experience furthermore contributes to the lesbian and gay movement's expressive dimension, which is of crucial strategic importance in contemporary American society.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; famille; familles homoparentales; his4443; homoparentalité; hétérosexisme; identités LGBTQIA2+; lesbianisme; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; parentalité; patriarcat; philosophie politique; premier cycle; queer; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; états-unis; études américaines

Scientificité et politique aujourd’hui : un regard féministe - Puig de la Bellacasa, María (Nouvelles Questions Féministes, 2003)
La richesse de la recherche féministe est en grande partie tributaire de la tension entre scientificité et engagement politique. Elle défie ainsi les définitions modernes de la scientificité et notamment la séparation entre science et politique. Cependant les enjeux liés à cette tension sont historiquement situés. Cet article propose une réflexion sur deux processus actuels qui peuvent affecter négativement cette singularité de la pensée féministe. D’une part, la précarisation du travail et la dégradation des rapports dans le monde académique. D’autre part, l’exigence actuelle d’une « pertinence sociale » des « produits » académiques.
Keywords: 1900-1999; 1970-1979; 1990-1999; angleterre; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; inégalités; patriarcat; premier cycle; pédagogie; périodes historiques; régions géographiques; science; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

The Logic of masculinist protection: Reflections on the current security state - Young, Iris Marion (Signs, 2003)
Keywords: amériques; approches et analyses; discipline; discours dominant; histoire et politique; masculinité; patriarcat; philosophie; philosophie politique; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; sécurité nationale; thématiques; états-unis